EFFECTIVENESS OF MOUTHWASHES BANANA AND PINEAPPLE PEEL EXTRACT AGAINST PLAQUE INDEX OF ORTHODONTIC FIXED PATIENT - Arya Prasetya Beumaputra; Pudji Handayani; Sofie Hana Regita Syehrun; Bella Aprilia Wulansari (JURNAL KEDOKTERAN DAN KESEHATAN, 2023)
Orthodontic fixed patients  used mouthwashes to control plaque chemically. Chemically mouthwashes have aftereffects in long-term use, which can have staining impacts  to teeth and mouth mucosa, aggravations in the working of the taste feelings of food, and  allergic reactions. Therefore, alternative mouthwash derived from herbs is required with the expectation that the risk of aftereffects is smaller. Banana and pineapple peel extract contain active antibacterial substances such as flavonoids, tannins, saponins, terpenoids, and bromelin. The purpose of this study is compare of the effectiveness of mouthwashes banana and pineapple peel extract in inhibiting plaque formation.This study was a quasi-experimental with pretest and posttest control group design involving 45 orthodontic patients as the subject of the study. The subjects were divided into three groups, namely the first group was given a mouthwashes banana peel extract of 2.5% (15 subjects), the second group was given a mouthwashes pineapple peel extract of 6.24% ( 15 subjects) and one control group (15 subjects) given a aquadest. The measurement of plaque index using Attin’s plaque index on before and after using mouthwash. Mouthwashes  banana peel extract 2.5% and pineapple peel extract 6.24% effective in lowering the plaque index of orthodontic fixed appliance patients. Mouthwashes banana peel extract is more effective in lowering plaque index. Banana peel extract mouthwashes are more effective in lowering the plaque index of   fixed orthodontic patients.